Deciphering the Dichotomous Effects of PGC-1α on Tumorigenesis and Metastasis - Gravel, Simon-Pierre (Frontiers in Oncology, 2018)
Metabolic reprogramming confers cancer cells the ability to grow and survive under nutrient-depleted or stressful microenvironments. The amplification of oncogenes, the loss of tumor suppressors, as well as context- and lineage-specific determinants can converge and profoundly affect the metabolic status of cancer cells. Cumulating evidences suggest that highly glycolytic cells under the influence of oncogenes such as BRAF, or evolving in hypoxic microenvironments, will promote metastasis through their impact on multiple steps of tumorigenesis such as the epithelial-to-mesenchymal transition (EMT). On the contrary, increased reliance on mitochondrial respiration is associated with hyperplasic rather than metastatic disease. The PGC-1α transcriptional coactivator, a master regulator of mitochondrial biogenesis, has recently been shown to exert anti-metastatic effects in cancer, notably through inhibition of EMT. Besides, PGC-1α has the opposite role in other cancers, in which it appears to provide growth advantages. Thus, the regulation and role of PGC-1α in cancer is not univocal, and its use as a predictive marker of outcome appears limited given its highly dynamic nature and its multi-faceted regulation by transcriptional and post-translational mechanisms. Herein, we expose key oncogenic and lineage-specific modules that finely regulate PGC-1α to promote or dampen the metastatic process. We propose a unifying model based on the systematic analysis of its controversial implication in cancer from cell proliferation to EMT and metastasis. This short review will provide a good understanding of current challenges associated with the study of PGC-1α.